2007
DOI: 10.1111/j.1460-9568.2006.05268.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of serotonin on perifornical‐lateral hypothalamic area neurons in rat

Abstract: The hypocretin (HCRT) system of the perifornical-lateral hypothalamic area (PF-LHA) has been implicated in the facilitation of behavioral arousal. HCRT neurons receive serotonergic afferents from the dorsal raphe nucleus. Although in-vitro pharmacological studies suggest that serotonin (5-HT) inhibits HCRT neurons, the in-vivo effects of 5-HT on HCRT neurons in the PF-LHA and associated behavioral changes have not been described. We examined the effects of 5-HT delivered locally into the PF-LHA using reverse m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
26
0
2

Year Published

2011
2011
2014
2014

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(31 citation statements)
references
References 41 publications
3
26
0
2
Order By: Relevance
“…The predictions about the monoamines, Avp, Ntsr, Trh, and Cck are supported by the literature (Bayer et al 2005;Tsujino et al 2005;Kumar et al 2007;Hara et al 2009), while the others are novel. Finally, we identify a novel set of transcription factors-including Elk3, Hmx2, Fosl1, Creb3l1, Rfx4, Stat5b, and Lhx9-that may be important for the specification of these cells.…”
Section: à5supporting
confidence: 60%
“…The predictions about the monoamines, Avp, Ntsr, Trh, and Cck are supported by the literature (Bayer et al 2005;Tsujino et al 2005;Kumar et al 2007;Hara et al 2009), while the others are novel. Finally, we identify a novel set of transcription factors-including Elk3, Hmx2, Fosl1, Creb3l1, Rfx4, Stat5b, and Lhx9-that may be important for the specification of these cells.…”
Section: à5supporting
confidence: 60%
“…This finding is supported by a recent report (Kaur et al, 2009) that identified the Hcrt -vPAG circuit, whose activity suppresses REM sleep but not non- REM sleep. On the other hand, Hcrt neurons receive inhibition innervation from noradrenergic (Li et al, 2002), serotoninergic (Yamanaka et al, 2003; Kumar et al, 2007) and dopaminergic (Yamanaka et al, 2006) inputs whereas the histamine has little, if any, effect (Yamanaka et al, 2003). The role of noradrenergic innervation to Hcrt cells remains controversial, as some reports show excitatory effects in rats and others demonstrate inhibitory action (Grivel et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…The placement of the microdialysis probe was such that it was adjacent to the microwire bundles and the extracellular environment of the recorded neurons was within the estimated diffusion field of the microdialysis probe (Alam et al, 2005, Kumar et al, 2007). The microdialysis probe was fixed and microwire bundles were advanced adjacent to the side of the exposed microdialysis membrane to minimize the tissue trauma and to ensure maximum stability of the unit recording.…”
Section: Methodsmentioning
confidence: 99%